Antígona, o fruto de uma cepa deformada Hélia Correia, Perdição (Nuntius Antiquus, 2008)
This Portuguese Antigone, inspired by the Sophoclean play, puts the accent on different topics. Following Antigone’s behaviour from her childhood, it creates a group of female characters around the heroine and aims at her development as someone growing up from a disturbed family. Her irreverency is not put in service of any ideal, it is the consequence of her desadaptation.